The Risk of Polygamy and Wives’ Saving Behavior - Boltz, Marie; Chort, Isabelle (Published by Oxford University Press on behalf of the World Bank, 2020)
In a polygamous society, all monogamous women are potentially at risk of polygamy. However, both the anthropological and economic literatures are silent on the potential impact of the risk of polygamy on economic decisions of monogamous wives. We explore this issue for Senegal using individual panel data. We first estimate a Cox model for the probability of transition to polygamy. Second, we estimate the impact of the predicted risk of polygamy on monogamous wives’ savings. We find a positive impact of the risk of polygamy on female savings entrusted to formal or informal institutions suggestive of self-protective strategies. This increase in savings comes at the cost of reduced consumption, both in terms of household food expenditures and wives’ private nonfood expenses.